When Judaism and Christianity Began. Vol. 1 : Essays in Memory of Anthony J. Saldarini - Avery-Peck, Alan J. (Supplements to the Journal for the Study of Judaism, 2004)
In these volumes, top scholars in the study of religion celebrate the enduring heritage in learning bequeathed to coming generations by Anthony J. Saldarini (1941-2001). Twenty-nine commemorative essays focus on the topical areas of formative Christianity and Judaism to which Dr. Saldarini devoted his efforts: earliest Christianity, with special attention to the Gospels; Judaism in late antiquity; and the interchange between Judaism and Christianity then and now. So too the disciplines represented in these pages match his history (including archaeology), literature, religion, and theology. Recognizing the standards of learning set by Dr. Saldarini in all of these areas, the colleagues represented in these volumes memorialize him by following in the model he set, of meeting the highest standards of the diverse fields that intersect in the study of Judaic and Christian antiquity. The print edition is available as a set of two volumes (9789004136595).